Pendampingan Pembelajaran Al-Qur’an Menggunakan Clasical Peraga Melalui Media Audio Visual di TPA Ar-Rasyid Palangka Raya - M.Luquman Hakim; Zaini Rahman; Surawan Surawan; Fitriani Fitriani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Abstract This study aims to improve the quality of learning to read the Qur’an for children at TPA AR-Rasyid through the application of the Iqro method. The Iqro method is an approach to learning to read the Qur’an that emphasizes conformity to the rules of tajwid and the use of songs and distinctive rhythms. This study uses a qualitative approach with the Participatory Action Research (PAR) methodology. The results of the study indicate that the application of the Iqro method at TPA Ar-Rasyid can improve students’ ability to read the Qur’an and foster their enthusiasm in studying the Qur’an. The Iqro method has proven effective in creating a generation of fluent Qur’an readers who are committed to the teachings of Islam